Escherichia Coli Contamination Test In Thai Tea Drinks In The Ayahanda Street Area In Medan Using The Mpn Method - Dorkas Dhea F. Mendrofa; Samuel Joshua Hamonangan Tua Rajagukguk; Suandy Suandy (International Journal Labs, 2025)
Thai tea is one of the drinks that are popular with urban people. However, the less hygienic processing and presentation process can be a source of microbiological contamination. This study aims to detect the presence of Escherichia coli in Thai tea drinks sold on Jalan Ayahanda, Medan, using the Most Probable Number (MPN) method. The research design was quantitative descriptive with a laboratory experimental approach, using ten samples from Thai tea sellers. The results showed that all samples were positive for coliform with an MPN value of 15 – 460 MPN/100 mL, eight samples were positive for the BGLB confirmatory test, and one sample (10%) was positive for E. coli in EMB media. Based on the SNI standard (0/100 mL), the positive sample was declared unfit for consumption. These findings confirm the importance of implementing good hygiene and sanitation in the processing and sale of beverages to ensure food safety.